FUNGSI TEREGULASI DARI INTERVAL TERTUTUP TERBATAS KE RUANG EUCLID - , YURISKA INDAH PERWIT ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In this final project, we discuss about regulated functions from [ ] into . The discussion of regulated functions from [ ] into refers to the definitions and characteristics of regulated functions, inverse functions on cell [ ] and the characteristics of the sequences of functions by inverse functions. The next discussion are about definitions of inverse functions on cell [ ]. In fact, the functions have not always the inverse functions because it must have the bijective functions but it can be find the inverse functions . Therefore, in this final project we must to explain the inverse functions . Then, we discuss the connection of continue monotone functions and convergence on cell [ ] into with definitions and characteristics.